Enhancing Acute Pancreatitis Prognosis: Combined Ultrasound and BISAP Score Approach - Muratbek Alymkulov, Allan Abdiev, Talant Omorov, Edilbek Kudaiarov, Ulan Zhusup uulu, Aitikeev Adilet, (Asian Journal of Pharmaceutics (AJP), 2025)
Acute pancreatitis (AP) is a common gastrointestinal disorder with varying severity, ranging from mild, self-resolving cases to severe cases with systemic complications and high mortality rates. Early identification of patients at risk of developing severe AP is crucial for optimizing treatment and improving patient outcomes. Methods: This retrospective observational study aimed to assess the effectiveness of combining ultrasound (US) morphological staging with clinical severity scoring systems for early risk stratification in patients with AP. The study included 96 patients with AP who were admitted to two tertiary healthcare facilities in Bishkek, Kyrgyzstan, between December 2010 and November 2020. Results: Patients underwent US evaluation within 24 h of admission, and the findings were categorized using a modified Balthazar scoring system. Clinical severity was assessed using the Bedside Index of Severity in AP (BISAP), Ranson criteria, sequential organ failure assessment score, and Modified Marshall score. The results showed a significant correlation between higher Balthazar stages on US and moderate-to-severe AP. Among the clinical scoring systems, BISAP demonstrated the best balance between sensitivity (87.5%) and specificity (61.5%) in predicting severe disease. Conclusion: The integration of US morphological staging with BISAP scoring showed promise for enhancing early risk assessment in AP, particularly in resource-limited settings where computed tomography may not be readily available. Further prospective multicenter studies are needed to validate the effectiveness of this combined approach and explore the incorporation of advanced imaging techniques and molecular biomarkers for improved patient stratification and management of AP.